2022
DOI: 10.3390/jpm12101581
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Personal Melanoma Polygenic Risk Information: Participants’ Experiences of Genetic Counseling in a Community-Based Study

Abstract: Personalized polygenic risk information may be used to guide risk-based melanoma prevention and early detection at a population scale, but research on communicating this information is limited. This mixed-methods study aimed to assess the acceptability of a genetic counselor (GC) phone call in communicating polygenic risk information in the Melanoma Genomics Managing Your Risk randomized controlled trial. Participants (n = 509) received personalized melanoma polygenic risk information, an educational booklet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is crucial to convey this information in a manner that clients can comprehend easily, take appropriate action upon, and uses their preferred language. The articles in this Special Issue underscore the importance of achieving these objectives to ensure the adoption of desired behaviors [15,16]…”
Section: Communicating Complex Information To Clients and Their Famil...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to convey this information in a manner that clients can comprehend easily, take appropriate action upon, and uses their preferred language. The articles in this Special Issue underscore the importance of achieving these objectives to ensure the adoption of desired behaviors [15,16]…”
Section: Communicating Complex Information To Clients and Their Famil...mentioning
confidence: 99%
“…It is crucial to convey this information in a manner that clients can comprehend easily, take appropriate action upon, and uses their preferred language. The articles in this Special Issue underscore the importance of achieving these objectives to ensure the adoption of desired behaviors [ 15 , 16 ]. The second link in the communication chain that Pedrazzani et al reported involves clients sharing their genetic information with family members.…”
Section: Communicating Complex Information To Clients and Their Famil...mentioning
confidence: 99%